Pharmacokinetics of antisense oligonucleotide drugs - M. R. Khaitov; V. V. Smirnov (LLC "Publisher OKI", 2013)
This review covers the pharmacokinetic characteristics of the various antisense oligonucleotide drugs. A comparison of the pharmacokinetics of drugs first and second generation. As well as the influence on the pharmacokinetics of the chemical modification of the molecule.